Did the pandemic influence telehealth use among Swiss emergency department patients? A sequential explanatory study. Issue 2 (15th February 2023) - Michel, Janet; Schmid, Sandra; Aebersold, Eli Ruben; Mettler, Annette; Sauter, Thomas Christian
Abstract : Objective: The aim of this study was to explore pandemic telehealth use among walk-in emergency department (ED) patients at Bern University Hospital. Design: As in sequential explanatory designs, quantitative data were collected first. To explain the quantitative results, telehealth use was explored qualitatively using an interview guide informed by the quantitative results. Setting: The University Hospital of Bern ED designed a follow-up cross-sectional study (baseline done in 2019) to assess telehealth use among ED walk-in patients during the pandemic (2021). Participants: We included participants of all age groups that had consented to a follow-up qualitative study and also ensured a gender and age balance. We aimed for data saturation that was achieved by the seventh key informant. A total of 11 key informants took part in the study. Results: Three main themes emerged, namely: (1) telehealth use means the use of a telephone for many; (2) telehealth has both remits and limits; and (3) perceived future telehealth opportunities and threats. Conclusion: The pandemic seems not to have increased telehealth use among walk-in ED patients. The slight increase observed in telehealth use among women seems related to the use of the COVID-19 app from trusted sites like the Federal Office of Public Health. Telehealth emerged as having remits, limits, opportunities and threats. The human factor preference emerged as very important to all key informants. The fear that telehealth threatens the human factor cannot be over emphasised. The telephone remains the biggest telehealth modality among Swiss ED walk-in patients.